Effectiveness of application technology-based basic life support training method on cardiopulmonary resuscitation accuracy: A Systematic Review - Mega Utami; Sidik Awaludin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Professionals' knowledge and abilities can be enhanced by the effective and efficient use of technology in BHD training. In order to better study and assess the impact of application-technology based basic life support training techniques on the precision of cardiopulmonary resuscitation procedures, we plan to assess the existing research, which was published between 2014 and 2024. Purpose: To examine application-technology-based basic life support training approaches affected the precision of cardiac resuscitation techniques. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Individuals who received Basic Life Support (BLS) training, I: Technology application-based BLS training method, C: Conventional BLS training method or no app-based training, O: Accuracy in performing cardiopulmonary resuscitation (CPR), and S: Randomized controlled trial. The article search was conducted systematically using the keywords: Basic Support